Finding The Data Hyponym and An Analysis of Novel “The Wild Robot by Peter Brown” - Anabella Tiara Zilullah; Hilma Safitri; Barbie Amoura Keyra; Dina Syaripatul Hikmawati; Galuh Septina Candra; Salwa Asy Syifa Dema; Sandy Anggriawan Wiharjo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the semantic relationships of hyponyms in Peter Brown's novel, The Wild Robot, focusing on how specific word choices contribute to meaning and categorization within the narrative. With a qualitative approach and based on the theories of Cruse (1986) and Lyons (1995), 20 hyponymic expressions were found in the novel. These expressions were then grouped into semantic fields, including animals, plants, technology, and residences. For example, the words "otter," "berries," and "solar panels" were analyzed for their hierarchical relationship to common words (hypernyms) through Cruse's "kind of" test. The results show that choosing specific vocabulary helps clarify meaning, strengthens worldbuilding, and deepens characterization. Primarily in children's literature, clarity and concreteness of meaning greatly assist the reader's understanding process. In addition to being a linguistic tool, hyponyms act as cognitive devices that help readers organize information in narratives. These findings suggest that the structure of hyponyms enriches themes such as identity, nature, and attachment, thereby enhancing the reading experience. This study contributes to the study of lexical semantics, especially in understanding the role of hyponymy in multimodal narrative texts.